2016
DOI: 10.1900/rds.2016.13.236
|View full text |Cite
|
Sign up to set email alerts
|

First-Trimester Maternal Serum Amino Acids and Acylcarnitines Are Significant Predictors of Gestational Diabetes

Abstract: ■ AbstractBACKGROUND: Current screening methods for gestational diabetes mellitus (GDM) are insufficient in detecting the risk of GDM in the first trimester of the pregnancy. Recent metabolomic studies have detected altered amino acid and acylcarnitine concentrations in type 2 diabetes (T2D). Because of the similarities between T2D and GDM, the determination of these metabolites may be useful in early screening for GDM. AIM: To evaluate the association between GDM and first-trimester maternal serum concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Alterations in glycine/serine/threonine serum metabolism in GDM have previously been reported during the third trimester of pregnancy [ 52 ]. Glutamine and threonine are decreased during late gestation [ 53 , 54 , 55 ], while glycine is significantly decreased during the first and third trimesters with GDM, as well as in non-pregnant cohorts with T2D [ 36 , 37 , 38 , 39 , 56 , 57 ]. Glutamine showed a significant interaction effect, with decreases in early gestation trending towards significance following a post-hoc analysis ( p = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in glycine/serine/threonine serum metabolism in GDM have previously been reported during the third trimester of pregnancy [ 52 ]. Glutamine and threonine are decreased during late gestation [ 53 , 54 , 55 ], while glycine is significantly decreased during the first and third trimesters with GDM, as well as in non-pregnant cohorts with T2D [ 36 , 37 , 38 , 39 , 56 , 57 ]. Glutamine showed a significant interaction effect, with decreases in early gestation trending towards significance following a post-hoc analysis ( p = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that maternal serum biomarkers are altered already in the first trimester of pregnancy in women who subsequently develop GDM. Studied markers include metabolites such as glycine and arginine, fatty acids, sex hormone binding globulin (SHBG), inflammatory markers, adipocyte-derived markers, placenta-derived markers, placental exomes and glycosylated (Sambucus nigra lectinreactive) fibronectin [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Foetal metabolism, as indicated by carnitine levels and amino acids, is related to the risk of preterm infants, maternal gestational age and neonatal development [23,24] . Dysglycaemia is an important link between maternal serum amino acids and carnitines [25] , maternal obesity/overweight [26] and maternal and foetal lipid pro les [27] . We explored the relationship between GDM uctuated in glycosylated hemoglobin levels of 5.5%-6.4%(as GDM a ) and neonatal carnitine levels and amino acids and their potential in uence on foetal growth.…”
Section: Discussionmentioning
confidence: 99%